St. Louis, Mo., Rev. Ordinances ch. 16, art. 2, §§ 688-689 (1887) - (:unkn) unknown (My University, 1887)
Not exceeding five pounds of gunpowder shall be allowed to be kept by any person or persons in any store, dwelling, building, or other place within the city, except that retailers or venders of gunpowder in small quantities may for that purpose keep any quantity not exceeding thirty pounds; provided, that the same shall also be kept in tin or metal canisters or stone jars, with good and closely fitted and well secured covers thereon; provided, also, that those parties now having magazines within the limits of the city are hereby allowed to store in such magazines such quantities of gunpowder as may be necessary for their business; provided, further, that giant powder, dynamite and nitro-glycerine shall not be stored in any place within the limits of the city, except in magazines as now located. § 689. Every retailer of gunpowder, giant powder, dynamite, nitro-glycerine or blasting powder, shall place on the building containing the same, over, or at the side of the front door thereof, a sign with the words "Powder for sale," printed thereon, in letters at least three inches in height, and shall notify the commissioner of public buildings in which portion of said store the said powder or powders are placed, which notice shall be kept of record in the said commissioner's office.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER